Археографічні студії професора Я.Калакури - Палієнко, М.Г.; Гирич, І.Б. (Український історичний журнал, 2017)
Розглядається внесок професора Я.Калакури в дослідження теоретичних та
методологічних проблем археографії, його підходи до визначення і трактування поняття «українська археографія». Проаналізовано публікації дослідника
з історії Київської археографічної комісії, формування археографічної школи
Університету св. Володимира, розвитку археографічних студій в Україні на сучасному етапі. The article analyses the professor Ya.Kalakura’s contribution to the research of theoretical
and methodological problems of archаeography, his approaches to the concept
of the Ukrainian archаeography’s definition. It is also considered the resear-
ches’ publications on the history of Kyiv Archаeographic Commission, the formation
of St. Volodymyr University’s archаeographic school as well as the development of
archаeographic
studies in Ukraine nowadays.